THE ANALYSIS OF ENDHOPORIC REFERENCE IN OPRAH’S INSPIRATIONAL GOLDEN GLOBAL SPEECH - Renny Andriani; Nai Supartini (IKIP Siliwangi, 2020)
The aims of the research is to know endhoporic reference in Oprah’s speech. This research use descriptive qualitative method. The writer choose a transcript about Oprah’s speech from the website Endophoric is diveded in two types, there are anaphoric and cataphoric. The result shows that endhoporic references can be found in each paragraph in Oprah’s speech. This research found that anaphoric predominate in Oprah’s speech because she refers to something that has mentioned at before. In this study there were six sentences that referred to anaphoric reference and only one sentence referred to the cathaporic reference. Anaphoric is the only reference related to cohesion.